Real World Web Services - Iverson, Will (O'Reilly, 2011)
The core idea behind Real World Web Services is simple: after years of hype, what are the major players really doing with web services? Standard bodies may wrangle and platform vendors may preach, but at the end of the day what are the technologies that are actually in use, and how can developers incorporate them into their own applications? Those are the answers Real World Web Services delivers. It's a field guide to the wild and wooly world of non-trivial deployed web services.